Application of the Inverse-Electron-Demand Diels-Alder Reaction for Metabolic Glycoengineering - Haiber, Lisa Maria; Kufleitner, Markus; Wittmann, Valentin (Frontiers in Chemistry, 2021)
The inverse electron-demand Diels-Alder (DAinv) reaction is an emerging biorthogonal ligation reaction that finds application in all areas of chemistry and chemical biology. In this review we highlight its application in metabolic glycoengineering (MGE). MGE is a versatile tool to introduce unnatural sugar derivatives that are modified with a chemical reporter group into cellular glycans. The DAinv reaction can then be used to modify the chemical reporter group allowing, for instance, the visualization or isolation of glycoconjugates. During the last years, many different sugar derivatives as well as reporter groups have been published. These probes are summarized, and their chemical and biological properties are discussed. Furthermore, we discuss examples of MGE and subsequent DAinv reaction that highlight its suitability for application within living systems.